The Impact of Smart Interactive Products on Sustainable Environmental Adoption (Al-Academy, 2025)
In the face of escalating environmental challenges, such as climate change and the depletion of natural resources, smart technological solutions have emerged as an effective tool for promoting sustainability. The research question is: How can these products transform from entertainment or technological tools into drivers of environmental change? This research aims to explore the impact of smart interactive products on the adoption of environmental behaviors, focusing on their interaction mechanisms with users and their optimal design. The results showed that smart personalization and symbolic feedback promote sustainable behaviors, but challenges such as "cognitive dissonance" and "tech fatigue" reduce their effectiveness. The study also emphasized the importance of integrating cultural and social dimensions into design to increase the acceptance of sustainable solutions, especially in non-urban communities. One of the most prominent conclusions is that true sustainability requires a comprehensive analysis of the product life cycle, not just focusing on the use phase. The local cultural and environmental context is also a crucial factor in the success of smart solutions, especially in communities with strong privacy. The research recommends adopting simple, culturally sensitive designs and enhancing collaboration between designers and environmental experts to achieve comprehensive sustainability